Abundances and implications of volatile‐bearing species from evolved gas analysis of the Rocknest aeolian deposit, Gale Crater, Mars. Issue 1 (29th January 2014) - Archer, Paul Douglas; Franz, Heather B.; Sutter, Brad; Arevalo, Ricardo D.; Coll, Patrice; Eigenbrode, Jennifer L.; Glavin, Daniel P.; Jones, John J.; Leshin, Laurie A.; Mahaffy, Paul R.; McAdam, Amy C.; McKay, Christopher P.; et al.
Abstract The Sample Analysis at Mars (SAM) instrument on the Mars Science Laboratory (MSL) rover Curiosity detected evolved gases during thermal analysis of soil samples from the Rocknest aeolian deposit in Gale Crater. Major species detected (in order of decreasing molar abundance) were H2O, SO2, CO2, and O2, all at the µmol level, with HCl, H2S, NH3, NO, and HCN present at the tens to hundreds of nmol level. We compute weight % numbers for the major gases evolved by assuming a likely source and calculate abundances between 0.5 and 3 wt.%. The evolution of these gases implies the presence of both oxidized (perchlorates) and reduced (sulfides or H‐bearing) species as well as minerals formed under alkaline (carbonates) and possibly acidic (sulfates) conditions. Possible source phases in the Rocknest material are hydrated amorphous material, minor clay minerals, and hydrated perchlorate salts (all potential H2O sources), carbonates (CO2), perchlorates (O2 and HCl), and potential N‐bearing materials (e.g., Martian nitrates, terrestrial or Martian nitrogenated organics, ammonium salts) that evolve NH3, NO, and/or HCN. We conclude that Rocknest materials are a physical mixture in chemical disequilibrium, consistent with aeolian mixing, and that although weathering is not extensive, it may be ongoing even under current Martian surface conditions.